The relationship between breaths taken and swimming performance in a 50-meter freestyle race - Matsunami, M.; Suito, H.; Funai, Y.; Taimura, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The 50m freestyle race is the event with the highest speed in the competitive swimming. To achieve a high swimming speed, the following are important, (1) increase propulsion and (2) minimize resistance (Toussaint & Beek, 1992). The front crawl stroke used in racing is considered to cause an increase in resistance and a reduction in propulsion, as the posture changes significantly due to respiratory movements (Pedersen et al., 2006). Further, it has been shown that it is necessary to reduce the number of breaths to as few as possible to avoid increasing the resistance in the 50m freestyle races (Pedersen et al., 2006). However, how many breaths should be taken during a 50m freestyle race was not indicated. The purpose of this study was to examine the relationship between the number of breaths during a race and the swimming performance results in a 50m freestyle event.